Effects of interaction of poplar-wheat intercropping system on soil quality and yield of wheat (Triticum aestivum L.) - Shweta, . (Bangladesh Journal of Botany, 2020)
The significantly higher wheat grain yield in open condition i.e. in control was recorded (4.33 t/ha) over to poplar intercropping. Under the poplar plantation, wheat yield significantly affected and paired row plantation (18 × 2 × 2 m spacing) provides significantly higher grain yield and to 5 × 4 m and 10 × 2 m spacing.